Meningkatkan Motivasi Belajar Anak Pada Keluarga Yang Mengalami Perceraian (Broken Home) - Fajar Utama Ritongga; Azzahra (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Learning motivation is a psychological condition that encourages a person to carry out learning activities. Motivation is one of the important factors that affect learning and learning outcomes, but the strength and weakness of a person's motivation is different, it is influenced by several factors such as ideals, student conditions, environmental conditions. From this motivation will encourage a child to continue to learn in order to achieve the expected goals, namely achievement in learning. The purpose of this study was to describe the learning motivation of children with a broken home background and the factors that influence it. This research was held at the Child Care Community (KOPA) Medan City. In the context of activities PKL I mini-project. The data collection method in this study used observation and in-depth interviews with the subject in question. The results showed that the subject of AI had poor learning motivation, as evidenced by the low motivational aspects of AI learning. This is evident from the low level of Navy attendance at schools. The truant behavior carried out by the Navy is caused by internal factors and external factors from the Navy itself. External factors that make the reason for AL skipping classes are subjects that they are not interested in or do not like. While the internal factor is from the Navy itself. Low motivation Also encouragement from family is one of the strongest internal factors that makes AL often skip school. The purpose of this program is stated to be achieved, this can be seen from the growth of learning motivation in order to increase the enthusiasm for learning and also increase the confidence of the client.